The ACTIVATE Digital Health Pilot Program for Diabetes and Hypertension in an Underserved and Rural Community - Kim, Katherine K.; McGrath, Scott P.; Solorza, Juan L.; Lindeman, David (Applied Clinical Informatics, 2023)
Background Community health centers and patients in rural and agricultural communities struggle to address diabetes and hypertension in the face of health disparities and technology barriers. The stark reality of these digital health disparities were highlighted during the coronavirus disease 2019 pandemic.Objectives The objective of the ACTIVATE (Accountability, Coordination, and Telehealth in the Valley to Achieve Transformation and Equity) project was to codesign a platform for remote patient monitoring and program for chronic illness management that would address these disparities and offer a solution that fit the needs and context of the community.Methods ACTIVATE was a digital health intervention implemented in three phases: community codesign, feasibility assessment, and a pilot phase. Pre- and postintervention outcomes included regularly collected hemoglobin A1c (A1c) for participants with diabetes and blood pressure for those with hypertension.Results Participants were adult patients with uncontrolled diabetes and/or hypertension (n = 50). Most were White and Hispanic or Latino (84%) with Spanish as a primary language (69%), and the mean age was 55. There was substantial adoption and use of the technology: over 10,000 glucose and blood pressure measures were transmitted using connected remote monitoring devices over a 6-month period. Participants with diabetes achieved a mean reduction in A1c of 3.28 percentage points (standard deviation [SD]: 2.81) at 3 months and 4.19 percentage points (SD: 2.69) at 6 months. The vast majority of patients achieved an A1c in the target range for control (7.0–8.0%). Participants with hypertension achieved reductions in systolic blood pressure of 14.81 mm Hg (SD: 21.40) at 3 months and 13.55 mm Hg (SD: 23.31) at 6 months, with smaller reductions in diastolic blood pressure. The majority of participants also reached target blood pressure (less than 130/80).Conclusion The ACTIVATE pilot demonstrated that a codesigned solution for remote patient monitoring and chronic illness management delivered by community health centers can overcome digital divide barriers and show positive health outcomes for rural and agricultural residents.
Keywords: diabetes mellitus; hypertension; telemedicine; codesign; patient participation; digital divide; consumer health informatics